The Impact of Transformational Leadership on Teacher Performance: An Organizational Psychology Perspective in Educational Institutions - Akhmaliah Siti Nailan; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
This study highlights the research gap regarding the impact of transformational leadership on teacher performance in educational institutions from the perspective of organizational psychology, which has not been widely discussed in Indonesia. The purpose of this study is to analyze how transformational leadership affects teacher motivation and performance. The method used is a qualitative approach with a case study at MIN Bandung. The research participants consisted of madrasah heads and teachers, with data collected through interviews, observations, and documentation, then analyzed using thematic analysis. The results of the study show that the transformational leadership of madrasah heads has a significant impact on improving teacher performance, especially through the influence of ideals, inspirational motivation, intellectual stimulation, and individual consideration. In conclusion, transformational leadership is able to increase teacher motivation and productivity, as well as create a work environment that is conducive to innovation and professional development.